Steroid hormones and their receptors in breast cancer - Welsh, JoEllen (Henry Stewart Talks, 2007)
Development and types of breast cancers, Molecular and cellular aspects of hormone action on breast cells, Natural and synthetic estrogens, Basis for endocrine therapies, Alternative/emerging therapeutic approaches, Strategies for breast cancer prevention
Archived at 2020/08/13